World of fatwas or the shariah in action - Shourie, Arun. (New Delhi, 2002)
Why women are "The greatest affliction", "Majority in hell" - The powers a husband has over his wives. Why believers must put on non - believers down, why they must put them out? Why slaughtering cows is "A great Islamic Act" even though the Quran does not even mention it? From the ideology of separateness to that of separation or What attitude must believers have towards a Non - Islamic country? Should they accept the discoveries of Science when these contradict what is stated in the Quran and Hadis?
Keywords: Fatwas